The ECG Characteristics of Patients With Isolated Hypomagnesemia - Yang, Yiheng; Chen, Cheng; Duan, Penghong; Thapaliya, Suman; Gao, Lianjun; Dong, Yingxue; Yin, Xiaomeng; Yang, Xiaolei; Zhang, Rongfeng; Tan, Ruopeng; Hui, Simei; Wang, Yue; et al. (Frontiers in Physiology, 2021)
Background Electrocardiographic (ECG) characteristics of patients with isolated hypomagnesemia are not well defined. We aimed to investigate these ECG characteristics in order to define clearly the features of isolated hypomagnesemia. Hypothesis Lower serum magnesium could affect ECG parameters after excluding potential confounders. Methods This retrospective study was of patients with low serum magnesium <0.65 mmol/L compared with the same patients after restoration to normal serum magnesium. Patients with hypokalemia, hypocalcemia and other electrolyte disturbances were excluded. ECG parameters manually determined and analyzed were P wave dispersion, PR interval, QRS duration, ST-T changes, T wave amplitude, T peak-to-end interval (Tpe), corrected Tpe (Tpec), QT, corrected QT (QTc), QT peak corrected (QTpc) and Tpe dispersion, Tpe/QT ratio. Results Two-hundred-and-fourteen patients with isolated hypomagnesemia were identified with 50 of them (56.9 ± 13.6 years; 25 males) being eligible for final analysis from 270,997 patients presenting April 2011–October 2017. In the period of isolated hypomagnesemia, P wave duration was found prolonged (p ≤ 0.02); as was QTc (439 ± 27 vs. 433 ± 22, p = 0.01). Tpec (122 ± 24vs. 111 ± 22, p = 0.000) and Tpe/QT ratio (0.29 ± 0.05 vs. 0.27 ± 0.05, p = 0.000) were increased. QTpc decreased during hypomagnesemia (334 ± 28 vs. 342 ± 21, p = 0.02). However, no significant differences were found in PR interval, QRS duration (85 ± 12 ms vs. 86 ± 12 ms, p = 0.122) and ST-T segments between the patients and their own controls. Conclusions In patients with isolated hypomagnesemia, P wave duration, QTc, Tpec, and Tpe/QT ratio suggesting atrial depolarization and ventricular repolarization dispersion were significantly increased compared with normal magnesium levels in the same patients after restoration to normal levels.